Phylogenetic patterns of ant–fungus associations indicate that farming strategies, not only a superior fungal cultivar, explain the ecological success of leafcutter ants. Issue 10 (9th May 2018) - Mueller, Ulrich G.; Kardish, Melissa R.; Ishak, Heather D.; Wright, April M.; Solomon, Scott E.; Bruschi, Sofia M.; Carlson, Alexis L.; Bacci, Maurício
Abstract: To elucidate fungicultural specializations contributing to ecological dominance of leafcutter ants, we estimate the phylogeny of fungi cultivated by fungus‐growing (attine) ants, including fungal cultivars from (i) the entire leafcutter range from southern South America to southern North America, (ii) all higher‐attine ant lineages (leafcutting genera Atta, Acromyrmex ; nonleafcutting genera Trachymyrmex, Sericomyrmex ) and (iii) all lower‐attine lineages. Higher‐attine fungi form two clades, Clade‐A fungi ( Leucocoprinus gongylophorus, formerly Attamyces ) previously thought to be cultivated only by leafcutter ants, and a sister clade, Clade‐B fungi, previously thought to be cultivated only by Trachymyrmex and Sericomyrmex ants. Contradicting this traditional view, we find that (i) leafcutter ants are not specialized to cultivate only Clade‐A fungi because some leafcutter species ranging across South America cultivate Clade‐B fungi; (ii) Trachymyrmex ants are not specialized to cultivate only Clade‐B fungi because some Trachymyrmex species cultivate Clade‐A fungi and other Trachymyrmex species cultivate fungi known so far only from lower‐attine ants; (iii) in some locations, single higher‐attine ant species or closely related cryptic species cultivate both Clade‐A and Clade‐B fungi; and (iv) ant–fungus co‐evolution among higher‐attine mutualisms is therefore less specialized than previously thought. Sympatric leafcutter ants can be ecologically dominant when cultivating either Clade‐A or Clade‐B fungi, sustaining with either cultivar‐type huge nests that command large foraging territories; conversely, sympatric Trachymyrmex ants cultivating either Clade‐A or Clade‐B fungi can be locally abundant without achieving the ecological dominance of leafcutter ants. Ecological dominance of leafcutter ants therefore does not depend primarily on specialized fungiculture of L. gongylophorus (Clade‐A), but must derive from ant–fungus synergisms and unique ant adaptations.